Duration of Water-Based Exercise on Hemodynamic and Sleep Quality: An of Hypertensives and Normotensives Subanalysis - Moura, Eliezer Guimarães; Bedoya-Castaño, Javier; de Andrade Barboza, Catarina; Silva, Gabriela; Dias, Gilmar; Ribeiro Ministro da Costa, Gabriela; Moreno, Heitor; Rodrigues, Bruno (Research quarterly for exercise and sport, 2025)
Purpose: This study aimed to determine whether a better hemodynamic profile and a better sleep quality are associated with the duration of physical exercise in the water; secondly, it aims to determine whether better sleep quality is associated with a more favorable hemodynamic profile. Methods: 97 subjects (85 women, age 59.46 ± 10.62) were included in the study. Groups were divided into normotensive (n = 46) and hypertensive individuals, (n = 51) duration of water aerobics (1-6 (n = 18), 7-11 (n = 11), 12-35 (n = 26), and > 36 months (n = 42), respectively), and sleep quality (Good, Poor, and Sleep Disordered). The peripheral (brachial), central (through applanation tonometry), and arterial blood pressure were assessed, and the Pittsburgh Sleep Quality Index questionnaire was collected. Results: We found that the groups practicing water-based exercise for a more extended period (>6 months) did not present improved pressure values and sleep quality. The best (though still weak) relationship between the water-based exercise time and the sleep quality values occurred between the group of 7-11 exercising for over 36 months (r = - 0.29 for both). When multivariate regression analysis was performed, there was interaction between AIx@75bpm and sleep quality score, as well as between AIx@75bpm and the age of subjects (p = .006 and 0.003, respectively). Conclusion: The data from the present study reported that subjects who participated for a longer time in the water aerobics training protocol had no additional hemodynamic and sleep quality benefits compared to volunteers with shorter duration groups (<6 months).